Porphyromonas gingivalis: A key role in Parkinson's disease with cognitive impairment? - Li, Dongcheng; Ren, Tengzhu; Li, Hao; Liao, Geng; Zhang, Xiong (Frontiers in Neurology, 2022)
Cognitive impairment (CI) is a common complication of Parkinson's disease (PD). The major feature of Parkinson’s Disease with cognitive Impairment (PD-CI) includes convergence of α-Synuclein and Alzheimer’s disease (AD)-like pathologies, neuroinflammation and dysbiosis of gut microbiota. Porphyromonas gingivalis (P. gingivalis) is an important pathogen in periodontitis. Recent researches suggest a role of P. gingivalis and its virulence factor in the pathogenesis of PD and AD, in particular concerning neuroinflammation and deposition of α-Synuclein and amyloid-β. Furthermore, in animal models, oral P. gingivalis could cause neurodegeneration through regulating the gut-brain axis, suggesting an oral-gut-brain axis may exist. In this paper, we discuss the pathological characteristics of PD-CI and the role of P. gingivalis in them.